The Mineralocorticoid Agonist Fludrocortisone Promotes Survival and Proliferation of Adult Hippocampal Progenitors - Gesmundo, Iacopo; Villanova, Tania; Gargantini, Eleonora; Arvat, Emanuela; Ghigo, Ezio; Granata, Riccarda (Frontiers in Endocrinology, 2016)
Glucocorticoid receptor (GR) activation has been shown to reduce adult hippocampal progenitor cell proliferation and neurogenesis. In contrast, mineralocorticoid receptor (MR) signaling is associated with neuronal survival in the dentate gyrus of the hippocampus, and impairment of hippocampal MR has been linked to pathological conditions such as depression or neurodegenerative disorders. Here, we aimed to further clarify the protective role of MR in adult hippocampal neurons by studying the survival and proliferative effects of the highly potent MR agonist fludrocortisone (Fludro) in adult rat hippocampal progenitor cells (AHPs), along with the associated signaling mechanisms. Fludro, which upregulated MR but not GR expression, increased survival and proliferation and prevented apoptosis in AHPs cultured in growth factor-deprived medium. These effects were blunted by the MR antagonist spironolactone and by high doses of the GR agonist dexamethasone. Moreover, they involved signaling through cAMP/protein kinase (PKA)/cAMP response element-binding protein (CREB), phosphoinositide 3-kinase (PI3K)/Akt and its downstream targets glycogen synthase kinase-3β (GSK-3β) and mammalian target of rapamycin (mTOR). Furthermore, Fludro attenuated the detrimental effects of amyloid-β peptide 1-42 (Aβ1-42) on cell survival, proliferation and apoptosis in AHPs, and increased the phosphorylation of both PI3K/Akt and GSK-3β, that was reduced by Aβ1-42. Finally, Fludro blocked Aβ1-42-induced hyperphosphorylation of Tau protein, which is a main feature of Alzheimer’s disease (AD). Overall, these results are the first to show the protective and proliferative role of Fludro in AHPs, suggesting the potential therapeutic importance of targeting MR for increasing hippocampal neurogenesis and for treating neurodegenerative diseases.